2018
DOI: 10.3390/met8070484
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tempering on the Microstructure and Properties of a High-Strength Bainite Rail Steel with Good Toughness

Abstract: An advanced bainite rail with high strength-toughness combination was produced in a steel mill and the effects of tempering on the microstructure and properties of the bainite rail steel were investigated by optical microscopy, transmission electron microscopy, electron back-scattering diffraction and X-ray diffraction. Results indicate that the tensile strength, elongation and impact toughness were about 1470 MPa, 14.5% and 83 J/cm 2 , respectively, after tempering at 400 • C for 200 min. Therefore, a high-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
1
11
0
2
Order By: Relevance
“…Mo as an alloying element is known to suppress the primary ferrite and pearlite and hence enhances bainite formation. [20][21][22][23] Based on the heat treatment procedure, Mo may exhibit secondary hardening in tempered steels. 20) Lately, studies on Q&P steels revealed that the Mo-containing alloy exhibited greater austenite fractions than the base alloy and in Mo-containing alloy, the stability of retained austenite is improved.…”
Section: Effect Of Isothermal Transformation Treatment and Tempering mentioning
confidence: 99%
“…Mo as an alloying element is known to suppress the primary ferrite and pearlite and hence enhances bainite formation. [20][21][22][23] Based on the heat treatment procedure, Mo may exhibit secondary hardening in tempered steels. 20) Lately, studies on Q&P steels revealed that the Mo-containing alloy exhibited greater austenite fractions than the base alloy and in Mo-containing alloy, the stability of retained austenite is improved.…”
Section: Effect Of Isothermal Transformation Treatment and Tempering mentioning
confidence: 99%
“…The book gathers manuscripts from academic and industrial researchers with stimulating new ideas and original results. It consists of one review paper regarding state of art and perspectives of alloys for aeronautic applications [1] and fifteen research papers [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] focused on different materials and processes.…”
Section: Contributionsmentioning
confidence: 99%
“…Zhu et al [14] report about a 1500-MPa-grade bainite rail developed and produced in an industrial production line. Nowadays, pearlite rail is widely used in the construction of railways, although high-speed and heavy-loading railways require steels with higher strength, toughness, and wear resistance.…”
Section: Contributionsmentioning
confidence: 99%
“…With regard to metal manufacturing, the relationship among process parameters, microstructure, and mechanical properties is fundamental in different areas (i.e., sintering, welding, casting, and plastic forming) and generally involves innovative and traditional fabrication methods [13].…”
Section: Introductionmentioning
confidence: 99%